Comparative Respiratory Tract Microbiome Between Carbapenem-Resistant Acinetobacter baumannii Colonization and Ventilator Associated Pneumonia - Xiao, Tingting; Guo, Qian; Zhou, Yanzi; Shen, Ping; Wang, Yuan; Fang, Qiang; Li, Mo; Zhang, Shuntian; Guo, Lihua; Yu, Xiao; Liao, Yulin; Wang, Chunhui; et al. (Frontiers in Microbiology, 2022)
Background: Carbapenem-resistant Acinetobacter baumannii (CRAB) is a common cause of ventilator-associated pneumonia (VAP) in intensive care unit (ICU) patients, but its infection and colonization state are difficult to distinguish. If the judgment is wrong, it may aggravate the abuse of antibiotics and further accelerate the evolution of drug resistance. We sought to provide new clues for the diagnosis, pathogenesis and treatment of CRAB VAP based on lower respiratory tract (LRT) microbiota. Methods: A prospective study was conducted on patients with mechanical ventilation from July 2018 to December 2019 in a tertiary hospital. Multi-genomics studies (16S rRNA amplicon, metagenomics and whole-genome sequencing [WGS]) of endotracheal deep aspirate (ETA) were performed. Results: Fifty-two ICU patients were enrolled, including 24 with CRAB VAP (CRAB-I), 22 with CRAB colonization (CRAB-C), and six CRAB-negative patients (infection-free) (CRAB-N). Diversity of pulmonary microbiota was significantly lower in CRAB-I than in CRAB-C or CRAB-N (mean Shannon index, 1.79 vs. 2.73 vs. 4.81, P<0.05). Abundances of 11 key genera differed between the groups. Acinetobacter was most abundant in CRAB-I (76.19%), moderately abundant in CRAB-C (59.14%), and least abundant in CRAB-N (11.25%), but its interactions with other genera increased in turn. Metagenomics and WGS analysis showed that virulence genes were more abundant in CRAB-I than in CRAB-C. Multi-locus sequence typing (MLST) of 46 CRAB isolates revealed that the main types were ST208 (30.43%) and ST938 (15.22%), with no difference between CRAB-I and CRAB-C. Conclusions: LRT microbiota dysbiosis including elevated relative abundance of Acinetobacter and reduced bacterial interactions, and virulence enrichment may lead to CRAB VAP. Keywords: Carbapenem-resistant Acinetobacter baumannii, Ventilator-associated pneumonia, Multi-genomics analysis, Microbiome, Virulence gene.